A41 Olfactory bulb atrophy and caspase activation observed early in the bachd transgenic lines. (September 2018) - Lessard-Beaudoin, M; Yu-Taeger, L; Laroche, M; Singer, E; Riess, O; Nguyen, HHP; Graham, RK
Abstract : Olfactory dysfunction is observed in several neurological disorders, including Huntington disease (HD), and correlates with global cognitive performance, depression and degeneration of olfactory regions in the brain. Despite clear evidence demonstrating olfactory dysfunction in HD patients, only limited details are available in murine models and the underlying mechanisms are unknown. In order to determine if alterations in the olfactory bulb (OB) are observed in HD we assessed OB morphology from 3 to 12 months of age in the BACHD rat models (TG5 and TG9). A significant decrease in OB weight was observed at 6 and 12 months of age compared to WT. We also detected increased mRNA and protein expression of mhtt in the OB of TG5 compared to TG9 at specific ages. Despite the higher expression of mhtt in the TG5 OBs, there was increased nuclear accumulation of htt in the OB of TG9 compared to WT and TG5 rats. As we observed atrophy of the OB in the BACHD rats we assessed for caspase activation, a known mechanism underlying the cell death observed in HD. We characterized caspase-3, –6, −8 and −9 mRNA and protein expression levels in the OB of the BACHD rat models at 3, 6 and 12 months of age. Early alterations in caspase mRNA and protein expression were detected in the TG9 and TG5 lines. However, the changes observed in the mRNA and protein levels are in some cases discordant, suggesting that the caspase protein modifications detected may be more attributable to post-translational modifications. The caspase activation studies support that cell death may be increased in the rodent HD OB and further our understanding of the olfactory dysfunction and the role of caspases in the pathogenesis of HD.